Healthcare Workers' Perceptions and Medically Approved COVID-19 Infection Risk: Understanding the Mental Health Dimension of the Pandemic. A German Hospital Case Study - Kuhlmann, Ellen; Behrens, Georg M. N.; Cossmann, Anne; Homann, Stefanie; Happle, Christine; Dopfer-Jablonka, Alexandra (Frontiers in Public Health, 2022)
Introduction. This study analyses how healthcare workers (HCWs) perceived risks, protection and preventive measures during the COVID-19 pandemic in relation to medically approved risks and organisational measures. The aim is to explore ‘blind spots’ of pandemic protection and make mental health needs of HCWs visible. Methods. We have chosen an ‘optimal-case’ scenario of a high-income country with a well-resourced hospital sector and low HCW infection rate at the organisational level to explore governance gaps in HCW protection. A German multi-method hospital study at Hannover Medical School served as empirical case; document analysis, expert information and survey data (n=1163) were collected as part of a clinical study into SARS-CoV-2 serology testing during the second wave of the pandemic (November 2020-February 2021). Selected survey items included perceptions of risks, protection and preventive measures. Descriptive statistical analysis and regression were undertaken for gender, profession and COVID-19 patient care. Results. The results reveal a low risk of 1% medically approved infections among participants, but a much higher mean personal risk estimate of 15%. The majority (68.4%) expressed ‘some’ to ‘very strong’ fear of acquiring infection at the workplace. Individual protective behaviour and compliance with protective workplace measures were estimated as very high. Yet only about half of the respondents felt strongly protected by the employer; 12% even perceived ‘no’ or ‘little’ protection. Gender and contact with COVID-19 patients had no significant effect on the estimations of infection risks and protective workplace behaviour, but nursing was correlated with higher levels of personal risk estimations and fear of infection. Conclusions. A strong mismatch between low medically approved risk and personal risk perceptions of HCWs brings stressors and threats into view, that may be preventable through better information, education/training and risk communication and through investment in mental health and inclusion in pandemic preparedness plans.